A comparison of explicit and implicit attitudes towards crop protection methods in Costa Rica and Germany. Issue 1 (1st January 2021) - Schaak, Henning; Römer, Ulf; Musshoff, Oliver; Montero Vega, Mercedes
ABSTRACT: Crop protection technologies and their usage are critically discussed issues, both in the public discourse and within the agricultural sector. However, attitudes towards different methods of crop protection have been primarily investigated through surveys thus far. Thus, explicit attitudes can be biased. Furthermore, they can differ between countries. The study aims to contribute to the understanding of explicit and implicit attitudes of two crop protection methods (chemical and genetically modified crop protection) in Costa Rica and Germany. The implicit attitude was measured by a single-category implicit association test. The test was conducted with a total of 441 agricultural students: 208 from Costa Rica and 233 from Germany. The results argue for regional heterogeneity in attitudes towards crop protection methods as genetically modified crop protection is perceived more positive in Costa Rica than in Germany. This might impact the regional acceptance of multilateral policies. The results also highlight the importance of the method selection for the elicitation of attitudes.